Comprehensive assessment of prognostic markers for sinonasal squamous cell carcinoma. Issue 8 (26th October 2013) - Takahashi, Yoko; Bell, Diana; Agarwal, Garima; Roberts, Dianna; Xie, Tong‐Xin; El‐Naggar, Adel; Myers, Jeffrey N.; Hanna, Ehab Y.
ABSTRACT Background Little is known about the molecular signature of the rare tumor sinonasal squamous cell carcinoma (SNSCC). The purpose of this study was to comprehensively assess various molecular biomarkers in SNSCC. Methods We chose 13 markers for this study, which have been known as prognostic markers in head and neck squamous cell carcinoma. Expression of these markers was examined by either in situ hybridization or immunohistochemical methods on tissue microarrays made from 70 SNSCC specimens and 28 matched‐pair normal tissues from patients who underwent surgical resection at our institution. Expression data were correlated with patient clinicopathologic parameters and survival. Results Of the 13 markers, only epidermal growth factor receptor (EGFR) protein expression was associated with significantly shorter disease‐free survival (DFS; p = .01307). EGFR expression was also associated with shorter overall survival (OS), but the difference was not statistically significant. Conclusion Targeted inhibition of tumor EGFR expression may be a new approach to treating SNSCC. © 2013 Wiley Periodicals, Inc. Head Neck 36: 1094–1102, 2014